Actinomycetes from the Soil of Chilli Plantation in Yogyakarta Showing an Antagonism to Fusarium oxysporum FU3 - Liya Audinah; Miftahul Ilmi (Jurnal Biodjati, 2019)
Application of biocontrol agent is an environmental-ly-friendly method to overcome the Fusarium wilt in chilli due to Fusarium oxysporum. This research aimed to isolate actinomycetes antagonist to F. oxysporum FU3 as biocontrol agent from the soil of chilli plantation in Kulon Progo, Yogyakarta. The actinomycetes were isolated using SCA medium and followed by screening for anti-F. oxysporum FU3 on PDA. The filtrate from isolates which showing the highest inhibition zone was produced and tested against strain FU3. The best isolate was then characterized. There are four iso-lates of actinomycetes showing antagonistic activity against F. ox-ysporum (AK4, AK5, AK7, and AK9). The highest antagonistic ac-tivity was shown by AK5 filtrate with inhibitions on PDA and PDB are 41.71 ± 3.5 % and 81.77 ± 5.1 %, respectively. Further obser-vation showed that filtrate of AK5 caused abnormality and lysis on FU3 hyphae. From the results, we concluded that AK5 is a poten-tial biocontrol agent against F. oxysporum. Further studies to opti-mize the production and formulize the bio-fungicide are suggested